Peroxisomal localization and circadian regulation of ubiquitin-specific protease 2. - Matthew M Molusky (PLoS ONE, 2012)
Temporal regulation of nutrient and energy metabolism is emerging as an important aspect of metabolic homeostasis. The regulatory network that integrates the timing cues and nutritional signals to drive diurnal metabolic rhythms remains poorly defined. The 45-kDa isoform of ubiquitin-specific protease 2 (USP2-45) is a deubiquitinase that regulates hepatic gluconeogenesis and glucose metabolism. In this study, we found that USP2-45 is localized to peroxisomes in hepatocytes through a canonical peroxisome-targeting motif at its C-terminus. Clustering analysis indicates that the expression of a subset of peroxisomal genes exhibits robust diurnal rhythm in the liver. Despite this, nuclear hormone receptor PPARα, a known regulator of peroxisome gene expression, does not induce USP2-45 in hepatocytes and is dispensible for its expression during starvation. In contrast, a functional liver clock is required for the proper nutritional and circadian regulation of USP2-45 expression. At the molecular level, transcriptional coactivators PGC-1α and PGC-1β and repressor E4BP4 exert opposing effects on USP2-45 promoter activity. These studies provide insights into the subcellular localization and transcriptional regulation of a clock-controlled deubiquitinase that regulates glucose metabolism.